Analisis Kesulitan Siswa Belajar Matematika pada Materi Operasi Penjumlahan dan Pengurangan pada Bilangan Cacah Kelas II di SDN 1 Demulih - Ari Trivena; I Wayan Numertayasa; Ni Putu Eni Astuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out the problems that make it difficult for students to learn the material on addition and subtraction operations in class II whole numbers at SDN 1 Demulih. This research focuses on answering questions related to how difficult it is for students to learn the material on addition and subtraction operations in class II whole numbers at SDN 1 Demulih. To answer this question, this research uses qualitative research using qualitative descriptive methods. The data collection used is observation, interviews and documentation. Meanwhile, in analyzing the data, researchers used quantitative descriptive analysis techniques. The results of this study found that class II students at SDN 1 Demulih experienced learning difficulties with the percentage of learning difficulties including 75% in understanding the concept of place value, 66.67% in addition procedures using saving techniques, 79.17% in the concept of